PENGARUH KETINGGIAN TEMPAT TERHADAP KANDUNGAN GIZI DAN ASAM OKSALAT PADA PELEPAH DAUN TALAS BENENG YANG TELAH DIBUDIDAYAKAN DI SEKITAR KAWASAN GUNUNG KARANG - Ningsih, Eltis Panca; Hermita, Nuniek (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
Talas beneng (Xanthosoma undipes K. Koch) is the local taro from Mountain Coral of Banten Province. This research was aimed to know the nutrient content, composition, oxalic acid and mineral content in the stem leaves of Talas Beneng are cultivated by the community at different places. The research was carried out from Maret until May 2017. This research was conducted in the form of field research around the area of Mountain Coral, Pandeglang Regency, Banten Province. Analysis of the stem leaves of Talas Beneng was done in PT. Saraswanti Indo Genetech, Bogor. The results showed that the content of proksimat stem leaves of Talas Beneng was cultivated include water, ash, protein, fat and carbohydrates. Moisture content at a higher altitude 200 m above sea level (asl): (93,90%) compared to the height of 400 m dpl (93,22%) and height of 800 m dpl (92,72%). Ash content at altitudes of 800 m asl was higher (0,73%) compared to the height of the 200 m asl (0,58%) and height of the 400 m asl (0,58%). Protein content at altitudes of 200 m asl was higher (0,48%) compared to the height of the 400 m asl (0,22%) and height of the 800 m asl (0,39%). Fat content at altitudes of 200 m asl, height of the 400 m asl and height of the 800 m asl is 0%. Carbohydrate content at altitudes of 800 m asl was higher (6,19%) compared to the height of the 200 m asl (5,04%) and height of the 400 m asl (5,98%). Content of oxalic acid (0,228%) at an altitude of 800 m asl higher than the height of the 200 m asl (0,195%) and the height of the 400 m asl (0,169%).Keywords: elevation, proximate, oxalic acid, talas beneng